A Revista TIME em uma perspectiva multidimensional - Souza, Renata Condi de (2012)
This thesis aims to analyze TIME magazine through its cover stories in search for the dimensions of linguistic variation of all of its texts since the beginning of its publication, in February 1923, to April 2011. To meet this goal, the research is based on Corpus Linguistics, an area of Applied Linguistics which sees language as a probability system and whose studies involve the use of computational tools and collections of texts held in electronic format (corpora). The research also finds support in Multidimensional Analysis, a corpus linguistic approach that allows the study of the dimensions of variation in large amounts of texts by means of statistical procedures in order to map the associations between linguistic features and registers. The methodology includes mass data collection of TIME magazine texts on the Internet through scripts and a range of analyses through Factor Analysis, Analysis of Variance and Cluster Analysis. The first part of the analysis aims at placing the corpus along the five main dimensions of variation defined by Biber in 1988, which apply to English as a whole. The second part of the analysis seeks to determine the dimensions of variation that are specific to TIME magazine as well as check the role of external circumstances, such as editorial, political, economic and social events. This reveals five dimensions, namely: person-oriented discourse versus discussion-oriented discourse, opinion-based stance, argumentative discourse versus action-oriented discourse, idea-oriented discourse versus actionoriented discourse, and covert persuasion versus informational reporting. Other analyses identify the ranges of variation within the dimensions, as well as the text types that are inherent in TIME magazine